Functional programming and multicore architectures – review of prior research (Revista Cientifica Ingenio Magno, 2016)
A bibliographical review is presented, aimed at identifying the fundamental concepts of functional programming, the different focuses and applications which have been given to this programming paradigm. In the second part the review centers on works aimed at the application and utilization of functional programming for parallel processing on multicore architectures. Finally it is concluded that thanks to the special characteristics presented, the functional paradigm has been gaining ground in different fields of application, and has gradually been incorporated in plans of study in university programs and the area of computing and related areas.
Keywords: functional programming; multicore architectures; parallel processing